Schools at the center of a public health emergency: leveraging schools for pediatric COVID-19 vaccination - Bode, Sara; Irwin, Mary Kay; Palme', Hannah; Skinner, Daniel (Frontiers in Public Health, 2023)
The U.S. Food and Drug Administration's expansion of COVID-19 vaccine eligibility in 2021 to include children presented opportunities and challenges to ensure widespread access. Children, and especially adolescents, were a crucial target population to reduce community positivity rates and support a resumption of in-person academics. Though existing school-based vaccination programs have demonstrated success in improving vaccination rates on an individual school level, best practice strategies for employing mass vaccination programs quickly in response to public health emergencies have yet to be identified. Through established partnerships, School Health Services at Nationwide Children's Hospital led a collaborative effort to employ a rapid, onsite school vaccination strategy across Franklin County for all eligible students. This collaboration resulted in a significant increase in vaccine access carried out through on-site vaccination clinics established in 20 local public and private school districts. Key strategies identified through the process included collaboration with school districts, local hospitals, and the public health department; calibrating program size to each site and number of vaccines needed; and coordination of team member roles. At the same time, experience with the effort also underscored key challenges and opportunities that future programs should consider, especially when operating in public health emergencies. School-based community health approaches targeting adolescents can increase vaccination rates, and can be successfully led by children's health systems in concert with public health departments and schools. At the same time, entities undertaking such efforts must plan in advance to ensure that partnerships can be effectively established with clear protocols for efficient and open communication, which is essential for overcoming barriers in access to healthcare services.